Word of Mouth dan Mobile Instant Messaging (Studi Pengaruh Word of Mouth Seputar Mobile Instant Messaging terhadap Preferensi Kawula Muda di Daerah Istimewa Yogyakarta dalam Memilih Mobile Instant Messaging) - , MARIA PRISCILLA BETEKENENG ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development of communication technology with the existence of new media have brought individuals, including youth to more interactive and dynamic communication patterns, include messaging activities, that is, the application of mobile instant messaging. Mobile instant messaging is one of the popular platform used in messaging, that has been used by many Indonesian citizens, especially youth in Daerah Istimewa Yogyakarta. Although in 2013, various mobile instant messaging applications used advertising in media to promote their product, the truth in the success of mobile instant messaging cannot be separated from word of mouth. Itâs because mobile instant messaging itself is community driven, where personal source individuals also affect the choice of individualâs mobile instant messaging, like seen in the phenomenom of increasing popularity of BlackBerry Messenger uses in Indonesia. From this, researchers are driven to understand if world of mouth also affect the preferences of youth in choosing mobile instant messaging. Daerah Istimewa Yogyakarta was chosen as the main area of research, because the most users of mobile instant messaging, youth, are located in this area. The research shown that a big proportion of respondents werekeen to receive information and reccomendations regarding mobile instant messaging from people they know. With quality contents and persuasive strength that are regarded quite good, word of mouth about mobile instant messaging gave influence to mobile instant messaging choices of youth in Daerah Istimewa Yogyakarta, although the influence was indirect. Utilitarian influence became influence factor that are more visible in their mobile instant messaging choices, where word of mouth encouraged a big proportion of respondents to choose mobile instant messaging that suits their personal sourceâs preference or reccomendations they received from their personal source.